10 kHz Spinal Cord Stimulation for the Treatment of Failed Back Surgery Syndrome with Predominant Leg Pain: Results from a Prospective Study in Patients from the Dutch Healthcare System. Issue 5 (22nd December 2020) - Kallewaard, Jan Willem; Gültuna, Ismail; Hoffmann, Vincent; Elzinga, Lars; Munnikes, Renate; Verbrugge, Lisette; Minne, Veerle; Reiters, Pascalle; Subbaroyan, Jeyakumar; Santos, Angela; Rotte, Anand; Caraway, David
Abstract: Introduction: Persistent back/and or leg pain is a common outcome after spinal surgery (otherwise known as failed back surgery syndrome [FBSS]). Studies have shown that spinal cord stimulation (SCS) at 10 kHz provides effective analgesia in FBSS patients with both back and leg pain symptoms and in those with predominant back pain. This study is the first to evaluate the therapy in FBSS patients with predominant leg pain. Methods: The safety and efficacy of 10 kHz SCS was evaluated in an uncontrolled, open‐label, prospective study of FBSS patients with predominant leg pain in the Netherlands. Follow‐ups were performed at 1, 3, 6, and 12 months post implantation. Results: Sixty out of 68 patients (88%) experienced sufficient pain relief during a stimulation trial. Of these, 58 proceeded to permanent implantation of a 10 kHz SCS system. After 12 months of treatment, 80% of patients experienced ≥ 50% reduction in baseline leg pain, and a similar proportion (76%) experienced ≥ 50% reduction in baseline back pain. At least two‐thirds of patients were also leg pain and back pain remitters (visual analog scale [VAS] ≤ 2.5 cm). The therapy was also associated with a general improvement in patients' quality of life, as measured by secondary outcomes including disability, perception of health improvement, mental well‐being, and satisfaction. A positive impact on opioid consumption was also observed. Conclusions: Consistent with previous findings, 10 kHz SCS for the treatment of FBSS patients with predominant radicular symptoms is safe and effective and is associated with improved quality of life.